Consumer attitudes towards electric vehicles: Effects of product user stereotypes and self-image congruence. (7th February 2018) - Bennett, Roger; Vijaygopal, Rohini
Abstract : Purpose: The purpose of this paper is to investigate the effects of gamification on connections between consumers' self-image congruence in relation to the purchasers of an environmentally friendly product electric vehicles (EVs) and their possession of a stereotype of EV owners as being "unconventional", and their attitudes towards EVs, having regard to their levels of environmental concern and prior knowledge of EVs. Additionally, the research explored the link between attitudes towards and willingness to purchase EVs. Design/methodology/approach: Participants completed a questionnaire and an Implicit Association Test (IAT) both before and after playing a computer game wherein the player assumed the identity of an EV driver. A structural equation model was constructed to predict attitude to EVs. The relationship between attitude and willingness to purchase was examined via a conditional process analysis. Findings: The experience of playing the game improved the favourability of the respondents' stereotype of EV owners by an average of 19 per cent, and their attitude towards EVs by 17 per cent. Self-image congruence in relation to EV ownership increased on the average by 14 per cent and reported EV product knowledge by 8 per cent. However, willingness to purchase an EV was not substantially affected. The link between attitude and willingness to purchase was weak, but was significantly moderated by stereotype favourability and self-image congruence with EV owners. Research limitations/implications: As with any IAT study, it was necessary to pre-specify a particular form of stereotype. Future research could employ alternative stereotypes. The investigation took place in a single country and involved a single environmentally friendly product. Practical implications: Gamification has much potential for helping manufacturers and government agencies to stimulate the mass market for EVs. To negate unfavourable images of EV owners, marketing communications promoting EVs might usefully employ celebrities, sports personalities and/or leading political figures as exemplars of the types of people who drive electric cars. Originality/value: The research is the first to explore the effects of gamification on product user self-image congruence and stereotype formation. It is novel both in its employment of an IAT to measure the consumer stereotype of an environmentally friendly product and in its examination of the moderating influences of stereotype and product user self-image congruence on the attitude-willingness to purchase link.